2020
DOI: 10.1016/j.resuscitation.2020.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Serum GFAP and UCH-L1 for the prediction of neurological outcome in comatose cardiac arrest patients

Abstract: Objective: Neurological outcome prediction is crucial early after cardiac arrest. Serum biomarkers released from brain cells after hypoxic-ischaemic injury may aid in outcome prediction. The only serum biomarker presently recommended in the European Resuscitation Council prognostication guidelines is neuron-specific enolase (NSE), but NSE has limitations. In this study, we therefore analyzed the outcome predictive accuracy of the serum biomarkers glial fibrillary acidic protein (GFAP) and ubiquitin C-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 36 publications
5
49
2
Order By: Relevance
“…197,201 A recent study of 717 patients reported that UCH-L1 and GFAP were optimal BB predictors of outcome as early as 24 h after cardiac arrest. 205 Use of BBs as an adjunct to other diagnostic modalities was recommended. Monitoring of plasma concentrations of GFAP and other brain injury biomarkers, including S100B and NSE, has also been shown to detect brain injury in children on extracorporeal membrane oxygenation (ECMO).…”
Section: Use Of Blood Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…197,201 A recent study of 717 patients reported that UCH-L1 and GFAP were optimal BB predictors of outcome as early as 24 h after cardiac arrest. 205 Use of BBs as an adjunct to other diagnostic modalities was recommended. Monitoring of plasma concentrations of GFAP and other brain injury biomarkers, including S100B and NSE, has also been shown to detect brain injury in children on extracorporeal membrane oxygenation (ECMO).…”
Section: Use Of Blood Biomarkersmentioning
confidence: 99%
“…Monitoring the status of possible CNS injury in these patients is vital given that cognitive deficits are observed even in ICU patients receiving care for other medical complications not associated with a primary brain injury. 199,205,241,[332][333][334] Even a year after leaving the ICU, many people experience PTSD, cognitive deficits, and depression. 335 Thus, the presence or absence of CNS injury in the ICU will be important in determining subsequent neurological deficits and neuropsychiatric problems.…”
Section: Clinical Applications In Acute Care Facilities and Emergencymentioning
confidence: 99%
“…Amongst many novel biomarkers that have been studied for brain injury after cardiac arrest, the most promising so far is neurofilament light (NFL), with an area under the receiver operating characteristic curve (AUROC) of 94-98% for discrimination of longterm neurological outcome as early as 24 h after ROSC [5,6]. Other biomarkers of brain injury, including S100 calcium-binding protein B (S100B), tau protein, glial fibrillary acidic protein (GFAP), and ubiquitin C-terminal hydrolase-L1 (UCHL1), have also shown potential in cardiac arrest prognostication [7][8][9][10][11]. Biomarkers of cardiac injury such as troponin T (TnT), N-terminal pro-B-type natriuretic peptide (BNP) and copeptin along with biomarkers of systemic inflammation such as procalcitonin (PCT) and interleukin-6 (IL-6) are also associated with neurological outcome [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 27, 2021. ; https://doi.org/10.1101/2021.05. 25.21257353 doi: medRxiv preprint surrogate markers of neuronal and astrocytic injury in non-neurological diseases like HIV [18][19][20] , cardiac arrest [21][22][23] and sepsis 24 as well. Among them, we measured six validated BIMs including glial fibrillary acidic protein (GFAP), neuron specific enolase (NSE), S100B, ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCHL1), Syndecan-1 and microtubule-associated protein 2 (MAP 2) in plasma drawn from hospitalized COVID-19 subjects and matched controls.…”
mentioning
confidence: 99%